Simulation of safe processes using aspen plus: an economic evaluation - Ajchariyapagorn, Araya; Douglas, Supaporn; Douglas, Peter L.; Pongamphai, Suwassa (2006)
A continuous process for the extraction of nimbin from neem seeds using supercritical CO2 was simulated using the AspenPlus™ simulation system. A mathematical model was built to simulate the extraction process and experimental data (Tonthubthimthong et al., 2001) were used to validate the model. The mathematical model of the complete process was coded in AspenPlus. Process simulation and optimisation, to minimise energy consumption, was carried out. Simulation and optimisation results are presented.